Experiments and numerical analyses of HB400 and aluminum foam sandwich structure under landmine explosion - Park, Juho; Choi, Hae-Jin (Composite structures, 2015)
Sandwich structures of HB400 armor steel and aluminum foam subject to buried mine blast were numerically and experimentally studied in this work. To be used in the FEM simulation model, the dynamic material properties of HB400 at high strain rates were characterized. The quasi-static compression tests of the aluminum foam were also performed to obtain its material properties. In order to characterize the behavior of HB400 armor steel and Al foam under mine explosion, TNT mine blast experiments and investigated the real time deformation and failures of the specimens. From the test results, we found that the aluminum foam core significantly reduce the maximum deflection and z-acceleration by absorbing blast impact energy. In our numerical analyses of the sandwich structure under landmine explosion, it is found that both of the CONWEP and CONWEP–JWL coupling techniques are applicable to the mine blast simulation; however, the enhanced blast pressure from the buried explosives should be considered by a scale factor of 2.3 comparing with the experiments.